Technology Acceptance Model in Supporting the Tendency to Use Applications and Impulsive Buying on Purchase Decisions - Dwi Azizah, Faradiva; Nur, Andi Nirwana (Manunggal Halim Jaya, 2022)
This article presents the results of the mapping carried out taken from various sources with a total of 20 articles that are used as mapping materials. Starting from 2004 to 2021. Based on existing theory, TAM consists of several factors, namely Risk Factors, Usefulness, and added value where the stronger these factors are, the stronger a technology can be accepted. The perceived ease can trigger impulse buying and purchasing decisions. The purpose of this study is to determine the relationship and correlation between TAM and impulse buying on purchasing decisions among students who use shopee e-commerce as a shopping medium.